Analysis of the Possibility of Limiting the Impact of Ground Vibrations Caused During Demolition of a Towers on Environment - TARGOSZ, Jan; BEDNARZ, Jarosław; LISOWSKI, Wojciech (Archives of Acoustics, 2016)
Before disassemble and demolition of five granulation towers the authors planned and carried out measurements of the intensity of vibrations induced during the fall of the dismantled components of towers on the ground. The main aim of the study was to determine the maximum permissible weight of falling elements of the towers during the demolition, in terms of ensuring the protection of buildings and equipment located in the vicinity of the works. It was unacceptable to increase the vibration amplitude displacement in each section of measurement on each of the three perpendicular axes by more than 2 μm peak-to-peak value and the absolute velocity of RMS of vibration amplitude couldn’t be increased by more than 1 mm/sec value than the background vibration during the demolition of the towers. Preliminary experimental studies were conducted on a test stand and the measurements were made on the real object. The amplitudes of vibration waves displacement and velocity were recorded on the measurement section in the direction of the protected building. The results of measurements were used to identify the propagation of the shock wave and the effectiveness of the proposed insulation layers.